2018
DOI: 10.1093/intimm/dxy050
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of CD69 in anti-tumor immunity through regulating the exhaustion of tumor-infiltrating T cells

Abstract: The introduction of immune checkpoint inhibitors in cancer treatment highlights the negative regulation of anti-tumor immunity, such as effector T-cell exhaustion in the tumor microenvironment. However, the mechanisms underlying the induction and prevention of T-cell exhaustion remain largely unknown. We found that CD69, a type II glycoprotein known to regulate inflammation through T-cell migration and retention in tissues, plays an important role in inducing the exhaustion of tumor-infiltrating T cells. Cd69-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 33 publications
7
69
1
Order By: Relevance
“…We found that transcripts including EPHA3, ICOS, ITGB2, ITGA3, ANXA1, CD3E, BTK, IL24, CDN1, IL2RA, IKZF1, RAB29, TNFSF4, CD1D, AIRE, and CD69, which have potential roles in T cell activation and cellular migration were upregulated in TIM-3 + , compared with TIM-3 − T cells ( Figure 3). These data are in accordance with some reports that the overexpression of CD69 [22], ICOS [23], and EPHA3 [24] have crucial roles in migration and metastasis of CRC. Moreover, genes including IL2RA, CD3E, CD69, and ICOS which have critical roles in survival and lymphocyte activation were also upregulated in TIM-3 + , compared with TIM-3 − T cells ( Figure 3).…”
Section: Transcriptomic Profile Of Cd4 + Tim-3 + Tils Reveals Their Psupporting
confidence: 93%
“…We found that transcripts including EPHA3, ICOS, ITGB2, ITGA3, ANXA1, CD3E, BTK, IL24, CDN1, IL2RA, IKZF1, RAB29, TNFSF4, CD1D, AIRE, and CD69, which have potential roles in T cell activation and cellular migration were upregulated in TIM-3 + , compared with TIM-3 − T cells ( Figure 3). These data are in accordance with some reports that the overexpression of CD69 [22], ICOS [23], and EPHA3 [24] have crucial roles in migration and metastasis of CRC. Moreover, genes including IL2RA, CD3E, CD69, and ICOS which have critical roles in survival and lymphocyte activation were also upregulated in TIM-3 + , compared with TIM-3 − T cells ( Figure 3).…”
Section: Transcriptomic Profile Of Cd4 + Tim-3 + Tils Reveals Their Psupporting
confidence: 93%
“…CD-69 sufficient state will cause effector T-cell exhaustion. The actual mechanism is still elusive; however, it is apparent that CD-69 expressed on leucocytes is responsible for cell retention in the tumor microenvironment and the CD-69 expression on T-cells is associated with the expression of PD-1 and Tim-3 in T-cells (67).…”
Section: Changes In Metabolite-and Cytokine-rich Tumor Microenvironmentsmentioning
confidence: 99%
“…In addition to its intrinsic value as an activation marker, CD69 is also an important regulator of immune responses 46 . Study had shown that CD69 plays a vital role in antitumor immunity by regulating the exhaustion of tumor-infiltrating T cells 47 . IKZF1 is a key regulator of a complex molecular signature governing immune infiltrate recruitment, making it both a predictor of response to therapy and an excellent candidate for future drug targeting 48 .…”
Section: Discussionmentioning
confidence: 99%